The attitudes of nursing students regarding the complementary and alternative medicine - Nursan Cinar; Funda Akduran; Dilek Kose (Universidade Federal de Goias, 2016)
The aim of this study was to determine the attitudes of nursing students towards complementary and alternative medicine. The sample consists of voluntary students (n=152) who had been present at school at the date of data collection. The data was collected via a questionnaire prepared by researchers and also via the "Holistic Complementary and Alternative Medicine Questionnaire (HCAMQ) which was developed by Hyland et al. (2003). The mean age of students was 20.09±1.6 (min=17, max=24). The mean score of scale was 25.41 ± 5.25 (min=11, max=45). The total score average of the first graders was 24.77±5.46, and of the last graders was 27.1±4.26. The difference between them was found to be statistically significant (t=-2.482, p=0.014). It is detected that more than half of the student nurses have no information about complementary and alternative medicine and that last graders, compared to the first graders, have a more negative attitude towards CAM applications.